The last Pleniglacial and the human settlement of Central Europe : new information from the Rhineland site of Wiesbaden-Igstadt - Streett, Martin
AMS and other dating methods have been applied to the problem of Upper Palaeolithic occupation in Central Europe. The results from the excavations at the Rhineland site of Wiesbaden-Igstadt provide an opportunity for comparison and discussion of whether central Europe was really subject to abandonment at various times during Glacial/Pleniglacial episodes.